Just What do Scholars do? A Qualitative Exploration of Text Analysis Tools for Information Visualization - Given, Lisa M.; Grotkowski, Ali (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper examines the use of text analysis tools by humanities scholars. The results of approximately 20 qualitative interviews with academics at different stages of career show both usability issues with current online tools and recommendations for future work in tool development. Implications for information system design are explored. Cette communication porte sur l’utilisation d’outils d’analyse de texte par les chercheurs en sciences humaines. Les résultats d’environ 20 entrevues qualitatives auprès d’universitaires à différents jalons de leur carrière relèvent des enjeux de convivialité d’utilisation pour les outils en ligne actuels et permettent de recommander des améliorations pour les outils. On y explore également les implications sur le design de systèmes d’information.